The Influence of Digital Marketing and Price Discounts on Steam Game Purchase Decisions - Marchellino william putra cahyono; Mariana Puspa Dewi (Al-Qalam Institue, 2026)
This study aims to examine the influence of digital marketing and price discount promotions on consumers’ purchase decisions of Steam games. A quantitative approach with an associative-causal research design was employed. Data were collected through an online questionnaire distributed to 100 active Steam users selected using purposive sampling. Multiple linear regression analysis was conducted using SPSS version 26 to test the proposed hypotheses. The results indicate that both digital marketing and price discount promotions have a positive and significant effect on purchase decisions, either partially or simultaneously. Among the two variables, price discount promotions demonstrate a stronger influence on consumers’ purchasing decisions compared to digital marketing strategies. These findings suggest that while digital marketing remains an important tool for increasing product awareness and engagement, discount-based promotions play a more decisive role in stimulating actual purchase behavior in digital game platforms. The study provides practical implications for digital game publishers and marketers to optimize promotional strategies by balancing persuasive digital marketing content with effective discount offerings to enhance purchasing outcomes.